Intravenous salbutamol for childhood asthma: evidence-based medicine?. Issue 9 (17th June 2014) - Starkey, E S; Mulla, H; Sammons, H M; Pandya, H C
Abstract : Intravenous salbutamol is commonly used to treat children with severe asthma unresponsive to inhaled β2-agonist therapy. However, in this setting, there is little clinical trial data demonstrating its effectiveness. Additionally, there are significant concerns that intravenous salbutamol-dosing recommendations for children with acute asthma are excessive, and unnecessarily raise the potential for adverse reactions, such as lactic acidosis and tachycardia which, by increasing respiratory workload, exacerbate respiratory failure. Here, we review salbutamol clinical pharmacology and toxicology, evidence relating to its use in acute asthma and highlight gaps in the evidence base.